Prevalence and predictors of left atrial thrombus in patients with rheumatic atrial fibrillation undergoing cardiac surgery: a cross-sectional study - Jie Cui; Yixiao Zhang; Yulin Wang; Fangyu Liu; Hao Lai; Qiang Ji; Chunsheng Wang (BMC Cardiovascular Disorders)
Abstract Background Unlike non-rheumatic atrial fibrillation (AF), where left atrial thrombus (LAT) is predominantly confined to the left atrial appendage (LAA), a significant proportion of LAT in rheumatic AF occurs within the left atrial cavity (LAC). However, LAC thrombosis in rheumatic AF has not been extensively studied. This study aimed to evaluate the prevalence of LAT and its subtypes and identify potential predictors of LAT. Methods This retrospective study included adult patients with rheumatic AF who underwent open-heart surgery for mitral valvular abnormalities between January 2019 and December 2020. LAT was identified through intraoperative inspection and categorized as either LAC thrombus or LAA thrombus. The prevalence of LAT and its subtypes was calculated, and logistic regression analysis was performed to identify predictors of LAT. Results A total of 530 patients (mean age: 59.7 ± 9.5 years; male: 29.8%) with a predominance of mitral stenosis (59.6%) were included. LAT was identified in 82 patients (15.5%), including 44 (8.3%) with LAA thrombus and 38 (7.2%) with LAC thrombus. In the multivariable logistic regression model, coronary artery disease (OR: 6.35, 95% CI: 2.79–14.46, p < 0.001), larger left atrial diameter (OR: 1.31 per 10 mm increase, 95% CI: 1.02–1.68, p = 0.03), and moderate-to-severe mitral stenosis (OR: 1.77, 95% CI: 1.00–3.13, p = 0.05) were independently associated with an increased risk of LAT, whereas moderate-to-severe mitral regurgitation was independently associated with a decreased risk of LAT (OR: 0.21, 95% CI: 0.11–0.43, p < 0.001). Conclusion In patients with rheumatic AF undergoing open-heart mitral valve surgery, LAT can be located in either the LAA or LAC. The presence of LAT was independently associated with coronary artery disease, left atrial enlargement, and mitral valvular abnormalities. Timely screening and management of LAT are crucial to mitigate potentially fatal thromboembolic events.